SWAT-UQ: A platform for uncertainty analysis, calibration and optimization of SWAT models - Mengtian Wu; Meihong Wu; Ruochen Sun; Xuan Huang; Shuo Yan; Jianjun Han; Qingyun Duan (Environmental Modelling & Software, 2026)

Modeling and characterizing errors in satellite and reanalysis precipitation estimates using a two-step decomposition procedure - Zhehui Shen; Mingze Ding; Ruochen Huang; Hao Wu; Bin Yong (Journal of Hydrology, 2026)

Research on Eliminating Knowledge Contradictions in the Field of Water Pollution Control Based on Extenics-Conjugate Analysis - Jianxun Li; Yujie Wu; Yanying Shang; Ruochen Zhang; Heng Lu (Water, Air, & Soil Pollution, 2026)

Whole genome sequencing reveals transmission dynamics and persistence of Listeria monocytogenes along the poultry slaughtering and processing chain - Ye Wang; Chaohui Huang; Sijie Wu; Jianye Jia; Tianxiang Pan; Ruochen Wang; Jing Li; Zegang Wang; Chuang Meng; Yuelan Yin; Xin'an Jiao (International Journal of Food Microbiology, 2026)

Dominant role of CaCl2 in integrated CO2 capture and utilization (ICCU-RWGS) in chloride-based molten salts - Xiaotong Zhao; Fangshu He; Ruochen Yang; Yulan Han; Xiong Zhang; Yang Yang; Haiping Yang; Chunfei Wu (Chemical Engineering Journal, 2026)

Urinary total arsenic, arsenic species, and arsenic methylation capacity: an integrative profiling analysis of microRNAs in plasma and leukocytes - Yaxin Wang; Wending Li; Weiya Li; Yufei Wang; Xuedan Xu; Ruochen Yuan; Xiao Zhang; Jingli Qu; Pinpin Long; Hao Wang; Meian He; Xiaomin Zhang; et al. (Environmental Pollution, 2026)

Deep eutectic solvent-assisted 3D printing of lignocellulosic biomass - Tingting Wu; Sigit Sugiarto; Udyani Aloka Weerasinghe; Ruochen Yang; Linran Jia; Pek Yin Michelle Yew; Danwei Zhang; Thenapakiam Sathasivam; Pei Lin Chee; Xunchang Fei; Dan Kai (Chemical Engineering Journal, 2025)

Community-level polycyclic aromatic hydrocarbon exposure and circulating microRNAs: Exploring their origins and regulatory functions in immune cells - Yufei Wang; Wending Li; Xuedan Xu; Yaxin Wang; Qin Jiang; Yutong You; Ruochen Yuan; Xiao Zhang; Yang Xiao; Chan Kong; Tingting Mo; Huan Guo; et al. (Journal of Hazardous Materials, 2025)

Intrinsic ion migration-induced susceptible two-dimensional phase-transition memristor with ultralow power consumption - Lanhao Qin; Yimeng Yu; Cheng Fang; Yujie Liu; Kaichen Zhu; Decai Ouyang; Shenghong Liu; Bailing Song; Ruochen Zhou; Mario Lanza; Wenhua Hu; Jinsong Wu; et al. (Science Bulletin, 2025)

CRISPR/Cas-powered “sweet” DNA nano-sponge for highly sensitive detection of pathogen nucleic acid with portable personal glucometer - Huiling You; Jingwen Shan; Yang Bai; Ruochen Yang; Shulin Tan; Yueqing Gu; Baicun Li; Haiping Wu; Yunlong Liu (Chemical Engineering Journal, 2025)

Surrogate modelling-based multi-objective optimization for best management practices of nonpoint source pollution - Aoyun Long; Ruochen Sun; Xiyezi Mao; Qingyun Duan; Mengtian Wu (Water Research, 2025)

Composite edible film mimicking cell wall based on arabinoxylan, β-glucan and nanocellulose: Microstructural, physico-chemical properties, and preservation effect - Yingting Li; Ruifeng Ying; Ruochen Wu; Meigui Huang (Food Bioscience, 2024)

Dairy farm waste: A potential reservoir of diverse antibiotic resistance and virulence genes in aminoglycoside- and beta-lactam-resistant Escherichia coli in Gansu Province, China - Muhammad Shoaib; Minjia Tang; Amjad Islam Aqib; Xuejing Zhang; Zhongyong Wu; Yang Wen; Xiao Hou; Jinpeng Xu; Ruochen Hao; Shengyi Wang; Wanxia Pu (Environmental Research, 2024)

The peculiar role of iodides and formation of iodinated oligomer byproducts upon phenol mineralization with boron-doped diamond anode - Ruochen Liu; Mingjun Ouyang; Shujuan Chen; Saier Wang; Chenwei Liu; Chunyong Zhang; Hua Wu (Chemical Engineering Journal, 2024)

Molecular characterization of petroleum acids from diverse geological origins via n-Butylsilane reduction - Haojie Hu; Shuofan Li; Yuanfeng Wang; Ruochen Yang; Jianxun Wu; Weilai Zhang; Chen He; Han Li; Yahe Zhang; Di Zhu; Quan Shi (Fuel, 2024)

Kinetic assessment of pulp mill-derived lime mud calcination in high CO2 atmosphere - Ruochen Wu; Edgar Carrejo; Md Sumon Reza; Ethan Woods; Seyedamin Razavi; Sunkyu Park; Fanxing Li; William Joe Sagues (Fuel, 2024)

Self-assembled multifunctional Prussian blue analogues nanocomposite for MRI-guided multimodal therapy for breast cancer - Min Zhang; Yanping Wu; Xingchen Lu; Yuhan Qin; Cong Zhang; Wenjie Gu; Ruochen Gao; Yuanyuan Qi; Meng Wang; Qingli Huang (Chemical Engineering Journal, 2024)

A knowledge-guided Estimation of Distribution Algorithm for energy-efficient Joint Robotic Assembly Line Balancing and Feeding Problem - Chu-ge Wu; Ruochen Zhang; Yuanqing Xia (Swarm and Evolutionary Computation, 2024)

A comprehensive investigation of three long‐term precipitation datasets: Which performs better in the Yellow River basin? - Ruochen Huang; Bin Yong; Fan Huang; Hao Wu; Zhehui Shen; Da Qian (International Journal of Climatology, 2024)
The fifth generation European Centre for Medium‐Range Weather Forecasts Reanalysis on global land surface (ERA5‐Land), the Multi‐Source Weighted‐Ensemble Precipitation (MSWEP), and the Climate Hazards Group Infrared Precipitation with Stations (CHIRPS) are three representative precipitation estimates with quasi‐global coverage, high‐resolution and long‐term record. This study concentrates on investigating, for the first time, the long‐term spatiotemporal accuracy and regional applicability of these precipitation estimates at a daily scale in the Yellow River basin (YRB) using 39 complete years of data record (1981–2019), with a special focus on their capability on monitoring the extreme precipitation events with short duration and the continuous heavy precipitation events. Results indicate that MSWEP generally performs better than ERA5‐Land and CHIRPS in almost all seasons and subregions, with the highest Pearson correlation coefficient and critical success index, lowest root mean square error and false alarm ratio. ERA5‐Land presents a severe overestimation of precipitation amount, particularly in the plateau climate region (BIAS = 52.27%), but well reflects its spatial–temporal patterns in the YRB. As for the detecting capability, MSWEP shows the best accuracy in detecting extreme precipitation, particularly in maximum consecutive 5‐day precipitation (RX5day). The MSWEP better represents the spatial distribution of maximum 1‐day precipitation and maximum consecutive 5‐day precipitation in the YRB, but it shows a significant overestimation in zone Southern Qinghai. MSWEP and CHIRPS have better performance of temporal variation consistency in annual precipitation with ground reference than ERA5‐Land, while ERA5‐Land performs well in capturing extreme precipitation temporal variation, especially for continuous heavy precipitation events. This study can provide useful guidance when choosing long‐term precipitation products for hydrometeorological applications and climate‐related studies in the YRB.

Suppression of phosphorus release and acceleration of sediment consolidation via exposure to sunlight and air (sunbathing) - Hao Hou; Wei Zhu; Jiming Liu; Xiaowei Lin; Ruochen Wang; Santao Xie; Hongyong Wu (Journal of Soils and Sediments, 2024)

One-step processing of waste dredged slurry into planting soil by targeted pretreatment and vacuum filtration - Silin Wu; Xiao Peng; Xiaohui Sun; Zijun Dong; Aizhao Zhou; Lei Zhang; Ruochen Wang (Journal of Environmental Management, 2024)

An integrated modelling framework for multiple pollution source identification in surface water - Xiaodong Liu; Xuneng Tong; Lei Wu; Sanjeeb Mohapatra; Hongqin Xue; Ruochen Liu (Journal of Environmental Management, 2023)

Fertilizing-induced alterations of microbial functional profiles in soil nitrogen cycling closely associate with crop yield - Ruochen Li; Chengyao Ren; Likun Wu; Xinxin Zhang; Xinyi Mao; Zhen Fan; Weili Cui; Wu Zhang; Gehong Wei; Duntao Shu (Environmental Research, 2023)

Weak environmental adaptation of rare phylotypes sustaining soil multi-element cycles in response to decades-long fertilization - Weili Cui; Ruochen Li; Zhen Fan; Likun Wu; Xining Zhao; Gehong Wei; Duntao Shu (Science of The Total Environment, 2023)

The increasing contribution of greening to the terrestrial evapotranspiration in China - Genan Wu; Xinchen Lu; Wei Zhao; Ruochen Cao; Wenqi Xie; Liyun Wang; Qiuhong Wang; Jiexuan Song; Shaobo Gao; Shenggong Li; Zhongmin Hu (Ecological Modelling, 2023)

Oceanospirillum sediminis sp. nov., Isolated From Coastal Sediment in the Yellow Sea - Huilin Zhao; Yue Tian; Xunke Sun; Qianwen Wu; Si Chen; Jiangfan Shan; Yu Zhong; Xinyu Chen; Xiaoxue Gao; Shengnan Liu; Ruochen Wang; Zongjun Du; et al. (Current Microbiology, 2022)

Mechanism of Water Inrush Through Fault Zones Using a Coupled Fluid–solid Numerical Model: A Case Study in the Beiyangzhuang Coal Mine, Northern China - Wenping Mu; Xiong Wu; Ruochen Deng; Qian Hao; Cheng Qian (Mine Water and the Environment, 2020)

Effect of silicate supplementation on the alleviation of arsenite toxicity in 93-11 (Oryza sativa L. indica) - Haichao Hu; Junting Zhang; Hong Wang; Ruochen Li; Fengshan Pan; Jian Wu; Ying Feng; Yeqing Ying; Qingpo Liu (Environmental Science and Pollution Research, 2013)